Prognostic significance of serum NLRC4 in patients with acute supratentorial intracerebral hemorrhage: A prospective longitudinal cohort study - Li, Wei; Lv, Xuan; Ma, Yijun; Cai, Yong; Zhu, Suijun (Frontiers in Neurology, 2023)
Objective Caspase activation and recruitment domain-containing protein 4 (NLRC4) is implicated in neuroinflammation. The aim of the study was to discern the potential ability of serum NLRC4 in assessment of prognosis after intracerebral hemorrhage (ICH). Methods In this prospective, observational study, serum NLRC4 levels were quantified in 148 acute supratentorial ICH patients and 148 controls. Severity was evaluated using the National Institutes of Health Stroke Scale (NIHSS) and hematoma volume, and poststroke 6-month functional outcome was estimated according to the modified Rankin Scale (mRS). Early neurologic deterioration (END) and 6-month poor outcome (mRS 3–6) were deemed as the two prognostic parameters. Multivariate models were established for investigating associations, and receiver operating characteristic (ROC) curves were configured to indicate predictive capability. Results Patients had substantially higher serum NLRC4 levels than controls (median, 363.2 pg/ml vs. 74.7 pg/ml). Serum NLRC4 levels had independent correlation with NIHSS scores [β, 0.308; 95% confidence interval (CI), 0.088–0.520], hematoma volume (β, 0.527; 95% CI, 0.385–0.675), serum C-reactive protein levels (β, 0.288; 95% CI, 0.109–0.341) and 6-month mRS scores (β, 0.239; 95% CI, 0.100–0.474). Serum NLRC4 levels above 363.2 pg/ml were independently predictive of END (odds ratio, 3.148; 95% CI, 1.278–7.752) and 6-month poor outcome (odds ratio, 2.468; 95% CI, 1.036–5.878). Serum NLRC4 levels significantly distinguished END risk [area under ROC curve (AUC), 0.765; 95% CI, 0.685–0.846] and 6-month poor outcome (AUC, 0.795; 95% CI, 0.721–0.870). In terms of predictive ability for 6-month poor outcome, serum NLRC4 levels combined with NIHSS scores and hematoma volume was superior to NIHSS scores combined with hematoma volume, NIHSS scores and hematoma volume (AUC, 0.913 vs. 0.870, 0.864 and 0.835; all P < 0.05). Nomograms were built to reflect prognosis and END risk of combination models, where serum NLRC4, NIHSS scores and hematoma volume were enforced. Calibration curves confirmed stability of combination models. Conclusions Markedly raised serum NLRC4 levels following ICH, in close relation to illness severity, are independently associated with poor prognosis. Such results are indicative of the notion that determination of serum NLRC4 may aid in severity assessment and prediction of functional outcome of ICH patients.